2021
DOI: 10.3390/ani11072087
|View full text |Cite
|
Sign up to set email alerts
|

Owners’ Knowledge and Approaches to Colic in Working Equids in Honduras

Abstract: In Honduras, many families are reliant on working equids in their daily life. The aim of this study was to evaluate knowledge about, and approaches to colic used by owners of working equids in Choluteca, Honduras using a phenomenological approach. Semi-structured, verbal questionnaires were conducted with ninety-three owners from eleven different communities in the Choluteca region on equid horse owners’ knowledge of colic and treatments. Additional context was gained through observations and verbal questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Although the diet of mules in this study were sufficient to support the maintenance of body condition in at least half of the cohort, the type and intervals for food intake are not appropriate for long-term health and welfare. Calorific, starch-based foods given without adequate access to water (Wild et al, 2021), and in the absence of limited access to adequate foraging opportunities to ingest foods of higher water and fibre content, can lead to gastrointestinal disturbances such as colic (Cohen et al, 1999;Curtis et al, 2019). Colic was reported by owners as being of concern and was witnessed and treated by the authors during the fieldwork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the diet of mules in this study were sufficient to support the maintenance of body condition in at least half of the cohort, the type and intervals for food intake are not appropriate for long-term health and welfare. Calorific, starch-based foods given without adequate access to water (Wild et al, 2021), and in the absence of limited access to adequate foraging opportunities to ingest foods of higher water and fibre content, can lead to gastrointestinal disturbances such as colic (Cohen et al, 1999;Curtis et al, 2019). Colic was reported by owners as being of concern and was witnessed and treated by the authors during the fieldwork.…”
Section: Discussionmentioning
confidence: 99%
“…Though there are many positive benefits of animal ownership it does not come without risks; the transmission of zoonotic diseases in the absence of adequate animal and human health programmes (Bettencourt et al, 2015), lack of owner awareness and lack of access to basic services increases risk of harm from disease transmission (Stringer, 2014). Many of the world's poorest people live in remote rural communities (FAO, 2022) and a lack of access to resources can have a real impact on the health and welfare of domestic animals (Letsoalo et al, 2000;Wild et al, 2021), people, on the wider environment and wildlife (Pinillos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported by Bowden et al (2020) . Rolling was also the most easily recognized clinical sign by horse owners in a prospective study conducted in Honduras ( Wild et al, 2021 ). Abnormal signs or signs observed only in the prodromal phase of colic and those that were considered mild symptoms of abdominal pain by the owner were not considered important in the decision-making for veterinary intervention.…”
Section: Discussionmentioning
confidence: 99%
“…These values are lower than those found in our study. A study by Wild et al (2021) found that 71% of horse owners in Honduras had previous experience of horses with colic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Guatemala, 85% of coffee is transported by WE (Chang et al 2010 ; Mosquera and Álvarez 2019 ). WE also transport firewood and water for household use, which are both vital enablers of food security for households (Wild et al 2021b ).…”
Section: Methodsmentioning
confidence: 99%